Peningkatan Inklusivitas Ekonomi Melalui Pembiayaan Investasi Modal Manusia - Kristyanto, Visi Saujaningati; Kaluge, David (Jurnal Ekonomi Kuantitatif Terapan, 2018)
At present, inclusive growth is a major issue in economic development. Inclusive growth encourages individuals to access education, health and other components that support a better standard of living. In East Java, high economic growth is followed by a high level of income inequality. The role of government is needed to encourage more quality growth through investment financing in the form of education and health investments. The purpose of this study is (i) to determine the relationship between financing of human capital investment and economic growth and (ii) to determine the impact of financing human capital investment on growth inclusiveness in East Java. The analysis method uses simultaneous regression method with two main equations. The findings show that financing of human capital investment has a significant effect on economic growth. This means that human capital investment can be used as an alternative policy to encourage economic growth in East Java. However, there is a problem that only a certain percentage of people with high levels of education, health and purchasing power enjoy economic growth. The second finding explains that inclusiveness can occur if the government encourages the effectiveness of financing the education sector which is still limited to increasing quantity but weak in the quality and productivity of the education sector. So that the existing human resource capacity is not able to encourage the creation of growth inclusiveness in East Java.
Keywords: pertumbuhan inklusif, pembiayaan pemerintah, investasi modal manusia,